Vatican Council II : the conciliar and post conciliar documents - Vatican Council (2nd: 1962-1965); Flannery, Austin (Northport, New York : Costello Publishing Company, 1984)
Contents: v.1 The Conciliar and post conciliar documents. v.2 More post conciliar documents
Includes bibliographical references and index
Keywords: Catholic Church -- Congresses; Vatican Council (2nd: 1962-1965)